Educação matemática: favorecendo investigações matemáticas através do computador. - Santana, José Rogério (2006)
The computerized resourses represents new perspectives and problems in the educational area with regard to the mathematics teaching. One of the present questions, consist in understanding as computer tools can favor the educational work and the learning studant. In this aspect, a common phenomenon consist in approach that favors the passage of the Old PC (PenCil) to the New PC (Personal Computer), however, this posture type relapses on the perspective of the type "it implemented in the computer, it worked, it ended". In this sense activities for school mathematical formation in computerized atmospheres turn not very reflexive and they end for valuing manipulations and simulations in detriment of the mathematical method through proofs and refutations. Taking these problems as base, in this work, I investigate the passage of the New PC to the Old PC as methodological possibility in educational terms for dimensioning the use of the computer in the mathematics teaching favoring the investigate process. The research consiste of understanding unexpected actions in educational software of mathematics, named by situation surprise. Starting from these, current of computacional restrictions, the idea consist of making possible structures you conjecture that demanded the mathematical argument or the validation process for demonstration. To understand the dinamical of this work it was investigated and it caracterized: i) situation surprise; ii) The procedures heuristics and deductive in the mathematical validation in the passage of the New PC to the Old PC in terms of teacher/studant; iii) That contributions the passage of the New PC to the Old PC could offer to the development and use of educational software of mathematics. The research made use of the didatic engineering while to favor the educational preparation in the context of the didatic situations, and for the posture of the researcher-teacher that used of the Fedathi´s Sequence. The field research in the school atmosphere happened in 3 stages that consisted of the teachers formation in the Military School of Fortaleza (CMF), formation how studants of 6a series of "EMEF Monteiro de Moraes", and final stage with studants of 8a series of CMF. The formations haved 40 hours/class was acomplished in these 3 stages. And for the transcription of video and questionnaries among other datas, it was possible to understand aspects of the passage of the New PC to the Old PC how an educational metodology that favors mathematical investigations through the computer. Experimentation situations and development were considered in educational software of mathematics. After transcription of the data was obtained 18 situations surprise, had given current of experimentation in the manipulation of educational in software of mathematics, and I tell about experience in the development of software GeoMeios. The results slowed that the situations suprise can elapse if computers limitations, but they also result of the action-instrumental accomplish the passage of the New PC to the Old PC in a reflexive and critical way the the educational ones and studants, and finaly, it was it was understood that the instrumental actions and the limatations relative of the computers to conceptual divergences to know mathmatical on the part of the developments they are actors that demand larger consideration in the perspective of the software engineening in educational terms.